(untitled) (Scientific journal of the Fergana State University, 2023)
The role of motives and symbols in the novel “God’s well” by Erkin Samandar, written in the years of Independence has been shon in the article. The novel begins with the epigraph, taken from the sacred “Koran”. According to the citation of the sacred book, the writer divides the characters of his novel into two groups: the group of people, who purged themselves from the sin; the second group, who could not purged. The writer depicted the heroes, who did not lose their trust and humaneness at any conditions, and took the motto of nobleness in the world, in spite of wars and disasters. The peoples’ acts are evaluated by the change of the colour of the water in the sacred well, converting from the transparent and clean into the muddy